Serving Together Towards a Healthy Society in An Effort to Implementation of Free Health Checks in Gadung Village Driyorejo District, Gresik Regency - M. Zaida, Andy Awwab; Pristanti, Adelia Dwi; Enggriana, Findi Nita; Wasilah, Nurul (Journal of Health Community Service, 2023)
Hypertension is a big problem in Indonesia. With increasing age, health problems are of course more and more suffered by the elderly, this is due to a decrease in the human immune system. Health problems that are often experienced are hypertension, cholesterol, gout. The aim of this activity is to improve the health of the people of Gadung Village through free health checks and health education as a preventive and promotive effort. This activity is a free health check for the elderly which is carried out for one day, starting with a survey to determine the location, time, equipment, and related parties who ensure the location is easily accessible and well prepared. Preparation involves planning activities, event concepts, and equipment such as tables, chairs, and medical equipment. The implementation of the activity was coordinated with the village head, midwives, and local nurses, taking place on July 31, 2023 at the Gadung Village Hall. The results of the activity showed positive achievements. Of the 48 participants who attended, most received direct benefits, such as health consultations and vitamin provision. Several participants who were detected as having diabetes complaints received follow-up in the form of medication and further medical advice from local midwives.